THE INFLUENCE OF THE FAMILY ON CHILDREN'S MENTAL HEALTH - Nadiya Zahrana; Sandy Lutan Mulyo; Andra Kasyifil Santoso; Rizky Pratama; Rifqi Adiyatma Farhan (PT. Radja Intercontinental Publishing, 2025)
Children's mental health is crucial for healthy growth and development, both physically and emotionally. One of the most significant influences is the family. This article summarizes various literature and research from the past five years, both domestic and international, that discuss how families shape and maintain children's mental health. From the various sources reviewed, it was found that the way parents raise their children, their communication with their children, their emotional stability, and the relationships between family members significantly influence children's mental health. This article also recommends greater family involvement in prevention and treatment programs for children's mental health issues, particularly in education and social policy.